Plant leaf disease identification - Hasan Mahin, Mohammad Rakibul; Moonwar, Waheed; Rayhan Chy, Md. Shamsul; Shahriar, Md. Fahim; Rafi, Fahim Faisal (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.